2022
DOI: 10.1111/1753-6405.13226
|View full text |Cite
|
Sign up to set email alerts
|

The COVID‐19 vaccine intentions of Australian disability support workers

Abstract: Objectives : Describe perceptions of COVID‐19, COVID‐19 vaccines, information sources, and levels and reasons for vaccine hesitancy among disability support workers (DSWs). Methods : Cross‐sectional survey of 252 DSWs from across Australia, between early March and early April 2021. Perceptions of risk of COVID‐19; government and media representations; vaccination status (Y/N); vaccine intentions (when offered, delayed vaccinators, vaccine refusers); reasons for hesitancy; con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…A handful of studies focused on the health of staff supporting people with ID and, within those studies, have also explored the mental health and well‐being of the people they supported (Hewitt et al, 2020 ; Kavanagh et al, 2020 ; Lunsky, Bobbette, Chacra, et al, 2021 ; McMahon et al, 2020 ; Navas et al, 2020 ). These studies have consistently indicated an increase in aggression, challenges with behavior, an increase in mental health issues, and heightened social isolation and loneliness among the people they were supporting.…”
Section: Methodsmentioning
confidence: 99%
“…A handful of studies focused on the health of staff supporting people with ID and, within those studies, have also explored the mental health and well‐being of the people they supported (Hewitt et al, 2020 ; Kavanagh et al, 2020 ; Lunsky, Bobbette, Chacra, et al, 2021 ; McMahon et al, 2020 ; Navas et al, 2020 ). These studies have consistently indicated an increase in aggression, challenges with behavior, an increase in mental health issues, and heightened social isolation and loneliness among the people they were supporting.…”
Section: Methodsmentioning
confidence: 99%
“…The last three studies from Europe (UK, Poland, and the Czech Republic) showed conflicting results regarding HCWs' acceptance of vaccine mandates for HCWs (acceptance rates: 6-75%) [37,40,57]. A generally supportive attitude was reported in a series of seven studies from the US, while data from two Australian studies revealed that Australian HCWs were divided about accepting COVID-19 vaccine mandates for HCWs [44][45][46][58][59][60][61][62][63]. In three studies (one from India, one from Mongolia, and one from Pakistan), most participants were in favor of vaccine mandates for COVID-19, while in another study from India, 60% of participants were against them [64][65][66][67].…”
Section: Main Findingsmentioning
confidence: 99%
“…In the context of the pandemic, the financial viability and sustainability of existing disability services into the future have been questioned in some quarters, and this line of questioning has inevitably also served to reduce the potential for any improvements to be forthcoming at this time (Bignal & Cassani, 2020 ; Kavanagh et al, 2020 ). While flexibility in funding mechanisms is needed (ANCOR Foundation and United Cerebral Palsy, 2021 ), vocational services largely bore the financial brunt of altered viability during lockdowns.…”
Section: Resultsmentioning
confidence: 99%
“…Underpinning any decision for continued service delivery within the COVID‐19 climate is the need for consideration of both service delivery approaches and the workforce itself—each of which is informed by the respective jurisdiction in response to the presence of the virus. In Australia, Kavanagh, Dimov, et al ( 2020 ) for example, captured the impacts for disability support professionals (DSPs) and identified that work place settings, similar to group homes, were not conducive to social distancing. However, the nature of support needs and health literacy of the people being supported, coupled with DSP knowledge about COVID‐19, infection control measures and varying levels of confidence with the use of PPE (personal protective equipment) still enabled them to engage in the required practice.…”
Section: Introductionmentioning
confidence: 99%